Web-Based E-Rapor Application Development Using Laravel 11 at SDN Burangkeng 05 - Arif Syarifudin; Helmi Prayogo Pangestu; Maulana Yusuf; Evita Fitri (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
The advancement of computer technology has significantly impacted the education sector, transitioning conventional learning methods into more digital-based approaches. However, many schools still manage academic assessments manually, which often results in inefficiencies, data inaccuracies, and limited access to academic information. The implementation of a digital academic system like e-Rapor offers a solution by enabling efficient and accurate data management, while also allowing parents to monitor student progress in real-time. This study focuses on SD Negeri Burangkeng 05 in Bekasi Regency, West Java, which still relies on manual processes using Microsoft Excel for academic reporting. The lack of a digital system has led to delays, limited data transparency, and difficulty in fulfilling administrative and accreditation needs. To address this issue, this research aims to develop an e-Rapor system suited to the school’s needs. The system is expected to improve academic data management, support administrative efficiency, and enhance the overall quality of educational services.